1999
DOI: 10.1046/j.1365-3156.1999.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolate resistance of Blastocystis hominis to metronidazole

Abstract: SummaryIsolates of Blastocystis hominis from infected immigrant workers from Indonesia, Bangladesh and infected individuals from Singapore and Malaysia were assessed for growth pattern and degree of resistance to different concentrations of metronidazole. Viability of the cells was assessed using eosin-brilliant cresyl blue which stained viable cells green and nonviable cells red. The Bangladeshi and Singaporean isolates were nonviable even at the lowest concentration of metronidazole at 0.01 mg/ml. The parasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 13 publications
4
40
0
2
Order By: Relevance
“…Eradication was observed in 4 of the 12 and 2 of the 9 patients treated with metronidazole and cotrimoxazole, respectively, indicating treatment failure in some patients with severe Blastocystis infections, possibly due to drug resistance. Studies have shown that Blastocystis strains isolated from patients may exhibit differences in sensitivity to metronidazole (92,292,316), ranging from 0.01 to 5 mg/ml, depending on the study. A report of isolates from IBS patients revealed 60% resistance to 0.1 mg/ml of metronidazole (292).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Eradication was observed in 4 of the 12 and 2 of the 9 patients treated with metronidazole and cotrimoxazole, respectively, indicating treatment failure in some patients with severe Blastocystis infections, possibly due to drug resistance. Studies have shown that Blastocystis strains isolated from patients may exhibit differences in sensitivity to metronidazole (92,292,316), ranging from 0.01 to 5 mg/ml, depending on the study. A report of isolates from IBS patients revealed 60% resistance to 0.1 mg/ml of metronidazole (292).…”
Section: Treatmentmentioning
confidence: 99%
“…A report of isolates from IBS patients revealed 60% resistance to 0.1 mg/ml of metronidazole (292). Another study of isolates from different geographical locations reported an Indonesian isolate showing resistance at 1.0 mg/ml metronidazole (92). The cyst form has been shown to be resistant (up to 5 mg/ml) to the cytotoxic effect of the drug (316).…”
Section: Treatmentmentioning
confidence: 99%
“…Fresh Blastocystis isolates, though, have been demonstrated to cause significant cytopathology of Chinese hamster ovary cells (CHO), adenocarcinoma HT-29 cells and rat intestinal epithelia (IEC-6) cells in culture (Puthia et al, 2006;Walderich et al, 1998). Metronidazole, paromomycin and ketoconazole have been used as therapeutic agents with mixed success (Zierdt et al, 1983;Dunn & Boreham, 1991;Haresh et al, 1999;Nanba et al, 2003). Although there have been some advances made concerning the morphology and cytochemistry of the organism, little is known of the biochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals infected with Blastocystis present with common intestinal symptoms, such as abdominal pain, vomiting, and bloating, as well as mucous and watery diarrhea (58). Blastocystis infections are commonly associated with dermatological disorders (25, 67) and irritable bowel syndrome (54).Although metronidazole (Mz) treatment is considered firstline therapy for Blastocystis infections, therapeutic intervention is equivocal because of the large number of asymptomatic carriers and frequent reports of treatment failure (3,23,37,53,55). The confusion concerning the status of Blastocystis as a pathogen is primarily due to limitations of diagnostic techniques, purported subtype-dependent variations in parasite virulence, and variable host responses (55).…”
mentioning
confidence: 99%
“…Although metronidazole (Mz) treatment is considered firstline therapy for Blastocystis infections, therapeutic intervention is equivocal because of the large number of asymptomatic carriers and frequent reports of treatment failure (3,23,37,53,55). The confusion concerning the status of Blastocystis as a pathogen is primarily due to limitations of diagnostic techniques, purported subtype-dependent variations in parasite virulence, and variable host responses (55).…”
mentioning
confidence: 99%